Estrategias didácticas para corregir la dislexia en el proceso enseñanza - aprendizaje del bloque 5, en el área de lengua y literatura en los niños y niñas del segundo grado del subnivel básica elemental, de la unidad educativa municipal La Pradera, del cantón y provincia de Loja, período lectivo 2013- 2014 - Riera Tenesaca, Rita Alexandra (2015)
Current education has generated, redefined and recreated a rich methodological heritage for educational and organizational work by implementing educational workshops that offer teaching strategies for learning and collaborative assessment, introducing the student in a process of evaluation, co-evaluation and self-evaluation, which allows correction of learning disabilities such as dyslexia, evaluation and monitoring, among others. This research addresses: Didactic strategies to correct dyslexia in the teaching-learning process of Block 5, Department of Language and Literature in children of second grade Sublevel Basic Elementary Education Unit Municipal La Pradera, the county and province of Loja, noting general objective raise and implement teaching strategies for children to correct dyslexia in the teaching-learning process for school year 2013-2014. El research development was supported by the methods: Synthetic Analytical, historical, deductive and inductive, bibliographic, statistical and method of the workshop. The techniques used were the evaluative test, interview and survey of the teacher. In perspective it was found that fourth graders have difficulties with memory, concentration and understanding, a situation that was offset by implementing teaching strategies that contributed significantly in correcting dyslexia presented in them, improving their learning Language and Literature; so it was established as a recommendation to implement other innovative teaching strategies to prevent the emergence of learning problems and counteract them.